Q: How do you graph the equation -7x - 4 equals 52?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

It's the equation of a straight-line graph. Every point on the line is a solution of the equation. There are an infinite number of them.

- 7X + 10 = 52 subtract 10 from each side - 7X + 10 - 10 = 52 - 10 - 7X = 42 divide both sides integers by - 7 (- 7/- 7)X = 42/- 7 X = - 6 --------------------check in original equation - 7(- 6) + 10 = 52 42 + 10 = 52 52 = 52 ----------------checks

7x+3y=-52 3(8x-y=-74) 7x+3y=-52 24x-3y=-222 7x=-52 + 24x=-222 31x=-274 x=8.8387

x=6

x = 6.4x + 10 + 3x = 52We can add the x's together (combine the terms) to get:7x + 10 = 52 (the plus 4x and the plus 3x become plus 7x here).Now we can combine the constants (the numbers) by moving the plus 10 to the same side of the equation as the plus 52. When we move something from one side of an equation to the other we must swap the sign (a plus becomes a negative and a negative becomes a plus). So we get:7x = 52 - 10 (in effect we have actually subtracted 10 from BOTH sides of the equation to keep the equation balanced).Now we simplify:7x = 42x = 42/7x = 6.

Related questions

Manipulate such that y is the subject of the equation 7x - 2y = -14 2y = 7x +14 y = (7/2)x + 7

It's the equation of a straight-line graph. Every point on the line is a solution of the equation. There are an infinite number of them.

The required equation is: -7x = 63

- 7X + 10 = 52 subtract 10 from each side - 7X + 10 - 10 = 52 - 10 - 7X = 42 divide both sides integers by - 7 (- 7/- 7)X = 42/- 7 X = - 6 --------------------check in original equation - 7(- 6) + 10 = 52 42 + 10 = 52 52 = 52 ----------------checks

7x+3y=-52 3(8x-y=-74) 7x+3y=-52 24x-3y=-222 7x=-52 + 24x=-222 31x=-274 x=8.8387

y=-10x-4

-2x + 8 = 7x - 10 is technically an equation, in and of itself.

x=6

x=6

x = 6.4x + 10 + 3x = 52We can add the x's together (combine the terms) to get:7x + 10 = 52 (the plus 4x and the plus 3x become plus 7x here).Now we can combine the constants (the numbers) by moving the plus 10 to the same side of the equation as the plus 52. When we move something from one side of an equation to the other we must swap the sign (a plus becomes a negative and a negative becomes a plus). So we get:7x = 52 - 10 (in effect we have actually subtracted 10 from BOTH sides of the equation to keep the equation balanced).Now we simplify:7x = 42x = 42/7x = 6.

-7 is.

7x + y = 8 Subtract 7x from each side of the equation: y = -7x + 8